DC Microgrid Deployments and Challenges: A Comprehensive Review of Academic and Corporate Implementations - Adewale W. Adegboyega; Saeed Sepasi; Harun Or Rashid Howlader; Brian Griswold; Marc Matsuura; Leon R. Roose (Energies)
DC microgrids are revolutionizing energy systems by offering efficient, reliable, and sustainable solutions to modern power grid challenges. By directly integrating renewable energy sources and eliminating the inefficiencies of AC-DC conversion, these systems simplify energy distribution and enhance performance in critical applications such as data centers, electric vehicle charging, and telecommunications. This review paper comprehensively examines the design, implementation, and performance of DC microgrids in real-world settings. Key components, including distributed energy resources (DERs), energy storage systems (ESSs), and control strategies, are analyzed to highlight their roles in ensuring reliability and operational efficiency. This review also explores the challenges facing DC microgrids, such as stability issues, protection mechanisms, and high initial costs, while offering insights into advanced control strategies and modular designs to overcome these obstacles. Through an evaluation of global case studies, this article bridges the gap between theoretical research and practical deployment and also demonstrates how DC microgrids can enhance energy efficiency, support sustainable power generation, and provide resilience in various applications. The findings highlight the potential of DC microgrids as a cornerstone of future energy systems, enabling clean, reliable, and decentralized energy solutions.